Major lessons for the CAP reform from the New Member States' perspective - Judith Möllers; Csaba Csaki; Gertrud Buchenrieder (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
The current discussion regarding the reform of the Common Agricultural Policy (CAP) is challenging due to the varying needs and interests of the old and new member states (NMS) of the European Union (EU). The NMS still display tremendous disparities in most structural and socio-economic indicators compared to the EU15 average, implying that further sectoral restructuring is needed. The Structural Change in Agriculture and Rural Livelihoods (SCARLED) project, which ran from 2007 until 2010, offers rich empirical insights with a specific focus on these processes in the NMS. This policy brief summarises the project's main policyrelevant results. SCARLED offers three key lessons for CAP reform. First, it claims that the current, uniform CAP only partially addresses the needs of NMS. Second, the region's agriculture still requires support to enhance competitiveness, albeit for a limited time. Third, the issue of small, subsistence-based farms in the region needs to be recognised. However, approaches aiming at poverty alleviation in such subsistence-based households, but also in landless rural households, need to look beyond the agricultural sector. The wider rural economy and improving education, as well as rural-urban linkages, need to be included in any povertyrelated policy approach, be it at the national or the EU level.
urn:nbn:de:gbv:3:2-31970
Keywords: 330